Comparison of the foot-ankle characteristics and physical and functional performance of racquet sport players - Ataç, Amine; Akıl Ağdere, Selin; Dilek, Burcu (AVES, 2023)
Objective: The aim of our study was to assess and compare foot–ankle characteristics and physical performances of different types of racquet sport players. Methods: The study was carried out with a control group and 3 racquet sports groups. Ten individuals were included in each group. Foot static and dynamic pressure distributions were assessed with a pedobarography device (FreeMed® Maxi; Sensor Medica®; Guidonia Montecelio, Rome, Italy). Functional performance parameters were evaluated with several tests. Differences between groups were evaluated with the 1-way analysis of variance test, and the Tukey’s Honestly Significant Difference Test (HSD) test was used as a post hoc test to determine the significant difference between groups. Results: There was no significant difference regarding pedobarographic variables between groups (P > .05). Blind Stork Balance Test parameters were found to be different between groups and significantly higher in the tennis group than the control group (P < .05). Modified Star Balance Test parameters were found to be different between groups, and results in table tennis players were found to be significantly higher than in badminton group (P < .05). Conclusion: As a result of this study, we could not detect any differences in pedobarographic variables in racquet sport players. Characteristic differences regarding physical performances were found in different kinds of racquet sports. There is a need for more extensive studies on this subject.
Keywords: Pedobarography; Performance; Racquet Sport; Tennis